Keusahawanan sosial Islam: faktor-faktor penglibatan usahawan sosial berjaya Muslim - Abd Muin, Mohd Adib; Abdullah, Shuhairimi; Bahari, Azizan (2016)
Islamic social entrepreneurship is one of the muamalat activities which became obligatory (fardu kifayah) to a community. Implementation of Islamic social entrepreneurship is very important because it fosters a positive relationship between man and his creator (Allah S.W.T) (hablum-minallah), man and man (hablum-minannas), and man and nature. The study of Islamic social entrepreneurship caters of maqasid syariah in preserve religion, life, intellect, lineage and property of those things that is detrimental or prejudicial. The objective of this study was to determining factors for successful Muslim social entrepreneurs in Islamic social entrepreneurship. Research methods used were Islamic epistemology, content analysis based on previous studies, and study library with a major revelation of the Qur'an and Sunnah. The results showed that there are several factors that drive successful Muslim social entrepreneurs implement social entrepreneurial activity among Muslims to seek a pleasure and blessings of Allah S.W.T in this world and the hereafter, to meet the needs of the goals and social vision of society, awareness of faith (iman) and piety (taqwa) are high in themselves, help solve social problems communities, become agents of change to the social economy, help youth gain the skills of social entrepreneurship, enhancing network cooperation with social business practitioners, monitor the performance of the youth, and to understand the purpose and social responsibility towards society.